Outcome of Femoral Angioplasty/Stenting Procedures in Different Ethnic Groups in England: A Retrospective Analysis of Hospital Episode Statistics and Review of Literature. (February 2023) - Vitalis, Antonios; Shantsila, Alena; Kay, Mark; Vohra, Rajiv K.; Lip, Gregory Y. H.
Purpose: Various studies, mainly from North America, report worse outcomes in ethnic minority populations submitted to revascularization for peripheral arterial disease (PAD). Limited nationwide data in relation to ethnicity are available from Europe. Objective: The objective of the study is to compare the outcomes of femoral angioplasty/stenting procedures among different ethnic groups in England during the 10-year period from 2006 to 2015. Materials and Methods: The "Hospital Episode Statistics" database has been searched using International Classification of Diseases, Tenth Revision ( ICD-10 ) codes to identify all cases of femoral angioplasty or stenting from English NHS Hospitals between January 1, 2006, and December 31, 2015. Subsequent mortality, second open or endovascular infrainguinal procedures, and major amputations on the same side within 2 years after the first procedure have been recorded. Patients were broadly categorized according to ethnicity as whites, Asians, and blacks. Chi-square test was used to demonstrate significant differences among ethnic groups and odds ratios (ORs) were calculated using white ethnic group as reference. Results: A total number of 70 887 femoral endovascular procedures were recorded in patients from the 3 ethnic groups. Two-year mortality in whites, Asians, and blacks was 18.3%, 22.1%, and 19.5% (p<0.001); rates of second endovascular procedure were 12.1%, 13.1%, and 13.5% (p=0.24); rates of open infrainguinal procedure were 5.6%, 4.5%, and 8.0% (p<0.001); and rates of major amputation were 4.8%, 4.1%, and 7.0% (p<0.001), respectively. Mortality was higher in Asians (OR=1.26, 95% confidence interval [CI]=1.10-1.45, p<0.01) compared with whites. On the contrary, blacks underwent more open arterial operations (OR=1.48, 95% CI=1.19-1.83, p<0.01) and more amputations (OR=1.49, 95% CI=1.18-1.87, p<0.01). There were no significant differences in the rates of second endovascular procedures. Conclusion: Two-year mortality after femoral angioplasty/stenting is higher in Asians, whereas risk of limb loss is higher in blacks compared with whites. Reasons of these ethnic differences in outcomes following femoral endovascular procedures for PAD merit further study.